2007
DOI: 10.1038/sj.eye.6702851
|View full text |Cite
|
Sign up to set email alerts
|

Developmental abnormalities of the optic nerve and chiasm

Abstract: Developmental anomalies of the optic nerve are an important and growing cause of lifelong visual handicap and they are often associated with systemic abnormalities. This review focuses on the ocular and systemic aspects of developmental anomalies arising from defects of fetal fissure closure and retinal ganglion cell development, and covers some other optic-disc anomalies that have systemic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 72 publications
(70 reference statements)
0
37
0
2
Order By: Relevance
“…In fact, the optic cup in vivo is not radially symmetrical and exhibits molecular and architectural differences along the nasal-temporal and dorsalventral axes. For example, in addition to differential expression of region-specific markers (Graw, 2010;Fuhrmann, 2010), the ventral-most region of the optic cup in the embryo has a characteristic gapped structure called the choroid fissure, which is formed by complex morphogenetic processes, including NR fanning and RPE back-folding (Adler and Canto-Soler, 2007;) (this fissure later closes by fusion and defects in this process cause coloboma; Taylor, 2007). The proximal region of the embryonic optic cup becomes the optic stalk (Fuhrmann, 2010), which could provide an intrinsic constraint for morphogenesis, whereas the hinge region gives rise to the ciliary margin, which harbours retinal stem cells later (Reh and Fischer, 2006).…”
Section: Reconciling In Vitro and In Vivo Datamentioning
confidence: 99%
“…In fact, the optic cup in vivo is not radially symmetrical and exhibits molecular and architectural differences along the nasal-temporal and dorsalventral axes. For example, in addition to differential expression of region-specific markers (Graw, 2010;Fuhrmann, 2010), the ventral-most region of the optic cup in the embryo has a characteristic gapped structure called the choroid fissure, which is formed by complex morphogenetic processes, including NR fanning and RPE back-folding (Adler and Canto-Soler, 2007;) (this fissure later closes by fusion and defects in this process cause coloboma; Taylor, 2007). The proximal region of the embryonic optic cup becomes the optic stalk (Fuhrmann, 2010), which could provide an intrinsic constraint for morphogenesis, whereas the hinge region gives rise to the ciliary margin, which harbours retinal stem cells later (Reh and Fischer, 2006).…”
Section: Reconciling In Vitro and In Vivo Datamentioning
confidence: 99%
“…Signs include a small neuroretinal rim, abnormal shape of nerve, optic nerve pallor, double ring sign, peripapillary abnormalities, abnormal vascular pattern, increased tortuosity, small or absent cup, fewer than normal vascular branching points, and disc diameter to disc macula ratio less than 0.3 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…19 Provis at al 20 investigated the number of axons of the human fetal optic nerve and found that at least 70% regress during pregnancy. These findings led Mosier et al 12 and other investigators 14,18 to propose the hypothesis that ONH is the result of excessive RNFL regression. McCulley et al 21 suggested that ONH may be the result of retrograde RNFL degeneration from axons not proceeding into the contralateral tract at the chiasm.…”
Section: Optic Nerve Head Changesmentioning
confidence: 99%
“…23 Alternatively, there could be a simultaneous effect on both the retina and the optic nerve as a result of genetic or environmental perturbation. In agreement with previous histopathologic studies in ONH, we observed thinning of nasal RNFL and temporal and nasal GCL using SD OCT. 13,14 Retinal nerve fiber layer and GCL loss in the macula have been described in patients with acquired optic nerve atrophy. 24e26 However, in contrast to histopathologic studies of optic nerve atrophy acquired later in life, we observed that patients with hypoplastic optic nerves also had continuation of the GCL, IPL, and OPL at the fovea and a differently shaped central fovea compared with healthy controls.…”
Section: Foveal Changesmentioning
confidence: 99%
See 1 more Smart Citation